2012
DOI: 10.2217/pme.12.117
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Comprehensive Diagnostic Assay for Scoliosis

Abstract: Adolescent idiopathic scoliosis (AIS) is one of the most common childhood deformities worldwide, characterized by a 3D spinal deformity with unknown cause, and represents both an immediate medical challenge and a chronic condition affecting individuals throughout their lives. The standard of care for scoliosis has not changed in any significant manner in decades. Patients today are treated in a substantially similar manner to those 20 or 30 years ago: observation, bracing and spinal surgery as last resort. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Furthermore, classification of AIS patients as a function of their biological endophenotype revealed that males classified in FG1 endophenotype showed significantly higher plasma YKL-40 levels than controls and AIS patients classified in the two other AIS endophenotypes. This is consistent with the fact that it is also widely known that males are less likely to develop severe forms of the disease when compared to females and we demonstrated previously that AIS patients classified in FG1 endophenotype are less likely to develop a severe spinal deformity when compared to the other endophenotypes 18 . This could be explained in part by the work of Aziz et al showing an elevation of circulating YKL-40 levels when testosterone levels are increased 26 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, classification of AIS patients as a function of their biological endophenotype revealed that males classified in FG1 endophenotype showed significantly higher plasma YKL-40 levels than controls and AIS patients classified in the two other AIS endophenotypes. This is consistent with the fact that it is also widely known that males are less likely to develop severe forms of the disease when compared to females and we demonstrated previously that AIS patients classified in FG1 endophenotype are less likely to develop a severe spinal deformity when compared to the other endophenotypes 18 . This could be explained in part by the work of Aziz et al showing an elevation of circulating YKL-40 levels when testosterone levels are increased 26 .…”
Section: Discussionsupporting
confidence: 92%
“…This could be explained in part by the work of Aziz et al showing an elevation of circulating YKL-40 levels when testosterone levels are increased 26 . Besides, testosterone, decreased circulating ghrelin levels in AIS patients exhibiting a non-progressive scoliosis 20,21 further support our results obtained with AIS patients classified in the endophenotype FG1 who are less likely to develop a severe scoliosis when compared to AIS patients classified in the other two endophenotypes 18 . Additional studies will be required to characterize the mechanism underlying the regulatory effect of ghrelin on YKL-40 secretion and/or expression in AIS and other conditions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…7 Most cases are diagnosed between 12 and 15 years of age and one out of every six will have a progressive curve that requires active treatment. 8 The etiology and pathogenesis of IS are poorly understood, largely due to the heterogeneity of related factors. 9 Some of the suggested etiological factors are growth pattern deviation, neuromuscular or connective tissue changes, asymmetric growth of the limbs and trunk, changes in the sagittal plane of the spine, environmental factors, and genetic influence.…”
Section: Introductionmentioning
confidence: 99%